STRATEGI KEPEMIMPINAN KIAI PADA PENINGKATAN MUTU PEMBELAJARAN - Winarto Winarto; Suyitno Suyitno; Linta Zahria (STKIP PGRI Situbondo, 2024)
The Al-Qur'an educational park or TPQ is classified as non-formal education which aims to realize tafaqquh fi al-din (deepening the Islamic religion) activities. Juridically, this kind of education is covered by Law of the Republic of Indonesia Number 20 of 2003 concerning the national education system and Government Regulation of the Republic of Indonesia Number 55 of 2007 concerning religious education and religious education. In article 14 in paragraph 2 it is stated that Al-Qur'an education is carried out in formal, non-formal and informal channels. Based on these regulations, TPQ has a big role in building the foundation of a child's character. In its realization, TPQ is equivalent to kindergarten (TK), meaning that religious education emphasizes providing basic lessons in reading the Koran. Meanwhile, learning the Koran at TPQ will play a strategic role in instilling Islamic character in children. TPQ learning is required to have pedagogical methods that are reliable, easy, and able to arouse students' interest in learning. Currently, TPQ is starting to compete in realizing quality TPQ management by emphasizing the content of character education in it. The strategic role of TPQ is deemed necessary to carry out research on how TPQ improves the quality of learning so that student output is quality and has character. The stages of the research method were carried out by observing, interviewing kiai, ustad, Islamic boarding school students, and carrying out documentation in the field. From these three stages, conclusions were drawn in order to find out and find novelty in this research. This research uses a qualitative approach to case study design, so that the researcher is the key to the research and is absolutely present at the research location. Next, the researcher will conduct in-depth interviews with Kiai, Ustad or Ustadah (respondents) intensively, preparing questions related to improving the quality of learning at TPQ. Research findings: Kiai as Figurehead/Symbol (leader, liaison, monitor, disseminator, and spokesperson as well as entrepreneur, disturbance handler, provider of all resources, and negotiator). The focus of this research is Kiai as Figurehead/Symbol (leader, liaison, monitor, disseminator, and spokesperson as well as entrepreneur, disturbance handler, provider of all resources, and negotiator.